2015 Systems and Information Engineering Design Symposium 2015
DOI: 10.1109/sieds.2015.7117006
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting energy trends and peak usage at the University of Virginia

Abstract: Forecasting energy trends, especially peak usage, is a valuable and necessary part of energy management. Accurate prediction allows for the control and alleviation of overuse during peak times with the implementation of energy efficiencies. Using hourly kilowatt data from over 200 buildings on the University of Virginia's campus this paper examines the most effective techniques for developing both individual building and overall grid use energy models with a specific focus on predetermining peak usage points. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…If the system is too small the probability of the power supply being insufficient increases, however, if the system is too large it results in unnecessary capital expenditure. Between 2006 and 2019 there were several investigations regarding load forecasting through time series analysis (Zala and Abhyankar, 2014;Heylman et al, 2015;Yilmaz et al, 2019;Zhu et al, 2019), and research done regarding optimal energy system design (Yang et al, 2009). These studies and their relevant results are discussed below.…”
Section: Energy Forcastingmentioning
confidence: 99%
See 2 more Smart Citations
“…If the system is too small the probability of the power supply being insufficient increases, however, if the system is too large it results in unnecessary capital expenditure. Between 2006 and 2019 there were several investigations regarding load forecasting through time series analysis (Zala and Abhyankar, 2014;Heylman et al, 2015;Yilmaz et al, 2019;Zhu et al, 2019), and research done regarding optimal energy system design (Yang et al, 2009). These studies and their relevant results are discussed below.…”
Section: Energy Forcastingmentioning
confidence: 99%
“…The papers evaluated various algorithms including regression, clustering, k-means, classification and neural networks, and concluded that a universal protocol capable of evaluating each algorithm for a specific set of input parameters is necessary to determine the optimal technique. Heylman et al (2015) investigated energy usage trends from over 200 buildings on the University of Virginia's campus to determine the most effective techniques for forecasting building energy usage. The study also examines the clustering of buildings based on their energy usage trends rather than the building's functional use.…”
Section: Energy Forcastingmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term predictions require analysis of time series, which are typically gathered over long time periods. In the time domain, the evolution of a given variable is usually modelled as a combination of trend, seasonal and cyclic patterns [21], [22]. While the trend represents the long-term decrease or increase, cyclic patterns are understood as rises or falls with no periodicity, and seasonality models the periodic changes.…”
Section: Introductionmentioning
confidence: 99%